Students Perceptions in Choosing Education to Higher Education - Nainggolan, Rolas Lodi Febri Ignatius; Sismudjito, Sismudjito; Munthe, Hadriana Marhaeni; Ismail, Rizabuana; Sitorus, Henry (Technium Social Sciences Journal, 2021)
This research describes how the choice to continue their education at the University of North Sumatra (USU) from the perspective of SMA Negeri 1 Sunggal students, starting from their perceptions of USU, their motivation to continue their education at USU, and how the environment influences their choice to continue their education at USU. The method used in this research is descriptive qualitative method, which describes phenomena based on actual conditions. The informants in this study were students who were in class XII SMA Negeri 1 Sunggal who were selected purposively based on their interest in continuing their education at USU. The data collection techniques used were in-depth interviews, participatory observation, and observation. The data that has been collected is then analyzed using descriptive qualitative analysis techniques to then draw a conclusion. The results showed that students considered continuing education at USU would make them smarter, because they would be taught by lecturers who were experienced and competent in their fields. In addition, USU is an institution that has been recognized for its existence in North Sumatra, and not everyone can become a student at USU. For some students, this is prestige in itself and raises the notion that being USU alumni can open up opportunities to get good jobs so that they can improve their family’s socioeconomic status. The choice to continue their education at USU is largely influenced by school and the peer group, while families are more likely to direct students to work after completing school. This condition is due to the fact that most students come from underprivileged circles, so that the financial contribution of each family member is very meaningful to maintain the survival of the family.